2004
DOI: 10.1073/pnas.0403681101
|View full text |Cite
|
Sign up to set email alerts
|

A small-molecule switch for Golgi sulfotransferases

Abstract: The study of glycan function is a major frontier in biology that could benefit from small molecules capable of perturbing carbohydrate structures on cells. The widespread role of sulfotransferases in modulating glycan function makes them prime targets for small-molecule modulators. Here, we report a system for conditional activation of Golgi-resident sulfotransferases using a chemical inducer of dimerization. Our approach capitalizes on two features shared by these enzymes: their requirement of Golgi localizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…Nevertheless, applications to immunofluorescence microscopy of cultured cells or tissue sections abound. Antibodies have been used for glycan visualization on fixed cells (52), as well as sections from chick cornea (53), bovine mammary gland (54), rabbit appendix (55), and human thymus (56), among others.…”
Section: Imaging Glycans With Lectins and Antibodiesmentioning
confidence: 99%
“…Nevertheless, applications to immunofluorescence microscopy of cultured cells or tissue sections abound. Antibodies have been used for glycan visualization on fixed cells (52), as well as sections from chick cornea (53), bovine mammary gland (54), rabbit appendix (55), and human thymus (56), among others.…”
Section: Imaging Glycans With Lectins and Antibodiesmentioning
confidence: 99%
“…Taken together, these data support a model where rapamycin-induced co-localization of the ubiquitin fragments (i.e., UbN and UbC) is not absolutely required for their complementation and GFP release. To test if this is the case, TTShld-GFP expressing HEK cells were treated with the same concentration of doxycycline (0, 50, 1000 ng/mL) and three different concentrations of FK-506 (0, 50, 500 nM), which will bind-to and stabilize FKBP* but not recruit FRB [13,14] . Analysis by western blotting (Figure 2C) showed that GFP was released in a similar dose-dependent manner compared to the cells that were treated with rapamycin (Figure 2B).…”
mentioning
confidence: 99%
“…This provided a powerful method for co-localising membrane-bound signalling proteins by incorporating a small-molecule binding domain; binding to a divalent chemical tool then allowed dimerisation to occur, and a signal to be read out to a reporter gene (Figure 4). This seminal work was later used to create conditional membrane co-localisation systems [42], adapted to heterodimeric systems [43], and continues to be used today for the switching of signalling and other membrane bound processes [44,45].…”
Section: Applications In Membrane and Signalling Processesmentioning
confidence: 99%